2020
DOI: 10.24198/jkg.v32i3.27480
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efek konsumsi kopi arabika berlebih selama masa laktasi terhadap densitas tulang mandibula anak tikus Wistar</p><p>The effect of excessive Arabica coffee consumption during lactation on the mandibular bone density of Wistar rats offspring</p>

Abstract: Pendahuluan: Laktasi merupakan periode penting dalam pertumbuhan dan perkembangan bayi. Salah satu faktor risiko yang menyebabkan penurunan densitas tulang mandibula adalah konsumsi kopi berlebih selama masa laktasi. Penelitian ini bertujuan untuk menganalisis pengaruh konsumsi kopi Arabika selama masa laktasi terhadap densitas tulang mandibula anak tikus Wistar. Metode: Penelitian eksperimental laboratoris dilakukan terhadap 12 ekor tikus Wistar betina yang sedang menyusui. Penghitungan besar sampel berdasark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…9 Other studies have suggested that mother mice that consume excess doses of coffee may have lower average value of mandibular bone density in rat cubs. 11 About 99% of caffeine in coffee will be directly absorbed by the intestines and transported around the body within 30-45 minutes. 12 Increased coffee consumption can cause an imbalance in calcium levels in the body, thus resulting in low level of calcium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Other studies have suggested that mother mice that consume excess doses of coffee may have lower average value of mandibular bone density in rat cubs. 11 About 99% of caffeine in coffee will be directly absorbed by the intestines and transported around the body within 30-45 minutes. 12 Increased coffee consumption can cause an imbalance in calcium levels in the body, thus resulting in low level of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other researchers also found that consuming Arabica coffee with an excess dose of 2.7 grams/200 grams body weight/day during lactation can reduce the density of the mandibular bones of Wistar rat cubs. 11 Considering these findings and limited references and research on radiographic images of calcified teeth of rat cubs, we seek to conduct an experimental study on the effect of Arabica coffee consumption during lactation on Wistar rats on radiographic images of calcified teeth of rat cubs.…”
Section: Introductionmentioning
confidence: 99%